IMPACT OF RISKS ON IJV PERFORMANCE IN PAKISTAN: MEDIATING ROLE OF EMC - Khan, Faisal Zaman; Iftikhar, Kamran; Durrani, Hina Gull; Siddiq, Ujala (The journal of contemporary issues in business and government, 2021)
The ongoing growth of the infrastructure development and construction industry in Pakistan in recent years has attracted foreign investors and firms to undertake Joint Ventures (JVs) in this emerging market, especially in the context of CPEC. The IJV paradigm is however quite complex and it is a general perception that usually the performance of JVs remains below the desired expectations. International construction businesses usually embody grave social, economic, and political implications in developing countries like Pakistan, where the problems of IJVs become more accentuated due to a host of other external as well as internal factors. Besides being an emerging trend, very few studies are available with regards to IJVs performance in Pakistan. This research is hence aimed at (1) Exploring the impact of Environment, Project and Partner’s Risks on IJVs performance (2) Develop a matrix for explaining the impact of risk factors and mediating role of Effective Management Control in IJV paradigm (3) To test the postulated hypothesis through quantitative methods. For this, a questionnaire-based survey has been conducted in which the feedback and perceptions from local and foreign firms and professionals have been recorded and analyzed using SPSS software. The study finds out that there are negative effects of Risks on IJV performance however, with Effective Management Control, the impact of risks are mitigated.